TEACHERS PROFESSIONALISM DEVELOPMENT STRATEGY TO INCREASE THE QUALITY OF GRADUATION; Case Study in SMK Al-Mukhtariyah, SMKN 5 Garut, and SMKN 6 Garut (STRATEGI PEMBINAAN PROFESIONALISME TENAGA PENDIDIK UNTUK MENINGKATKAN MUTU LULUSAN; Studi Kasus pada SM - Ajat Rukajat (Fakultas Agama Islam Universitas Wiralodra, 2019)
This study discusses the Teachers Professionalism Development Strategy which is part of the management in the world of education. This study aimed to obtain information about how the coaching strategy professionalism of educators to improve the quality of teachers in some vocational schools in Garut regency. The approach used in this study is descriptive qualitative, with the main descriptive-analytic method that comes with the method of documentation and literature. Data were collected by using observation, interviews, document study, questionnaire,andfieldnotes. The results showed that the educators at SMK Al-Mukhtariyah, SMKN 5 Garut, and SMK 6 Garut still rely on the role of school principals to foster professionalismenya, because the principal has a very important role in fostering the teaching staff in carrying out their duties, of course this will increase the quality of education through the various stages fromplanning, implementation and monitoring. With all the obstacles that are found mainly in complementary facilities and infrastructures as well as the allocation of funding is very minimal but the vocational school in Garut regency still able to carry out the training of the teachers who impacted the increasing creativity, competence, attitudes skilled and responsible attitude and to improve the effectiveness and efficiency process of coaching students personnel. Penelitian ini membahas mengenai Strategi Pembinaan Profesionalisme Tenaga Pendidik yang merupakan bagian dari suatu manajemen dalam dunia pendidikan. Pendekatan yang digunakan dalam penelitian ini adalah deskriptif kualitatif, dengan metode utama deskriptif-analitik yang dilengkapi dengan metode dokumentasi dan studi literatur. Data dikumpulkan dengan menggunakan teknik observasi, wawancara, studi dokumentasi, kuisioner, dan catatan lapangan. Hasil penelitian menunjukkan bahwa tenaga pendidik di SMK Al-Mukhtariyah, SMKN 5 Garut dan SMKN 6 Garut masih mengandalkan peran dari kepala sekolah untuk membina profesionalismenya, karena kepala sekolah mempunyai peran yang sangat penting dalam membina para tenaga pendidik dalam menjalankan tugasnya, tentunya hal ini akan meningkatkan mutu pendidikan melalui berbagai tahapan mulai dari perencanaan, pelaksanaan dan pengawasan. Dengan segala hambatan-hambatan yang ditemukan terutama dalam melengkapi sarana dan prasana serta alokasi pembiayaan yang sangat minim tetapi SMK di Kabupaten Garut tetap mampu melaksanakan pembinaan para tenaga pendidiknya yang berdampak meningkatnya kreativitas, kompetensi, sikap terampil, dan sikap tanggung jawab serta meningkatkan efektivitas dan efisiensi proses pembinaan tenaga didik.